2021
DOI: 10.1108/aeds-09-2020-0209
|View full text |Cite
|
Sign up to set email alerts
|

Social interaction and effectiveness of the online learning – A moderating role of maintaining social distance during the pandemic COVID-19

Abstract: PurposeThe pandemic of COVID-19 has pushed most of the classroom learning to an online environment with which most of the people were not familiar. This study aims to investigate the importance of social interaction on the effectiveness of online learning during the pandemic when social distancing norms are in place.Design/methodology/approachThis study uses the partial least square (PLS) structural equation modeling (SEM) approach, a nonparametric method based on total variance, using the SmartPLS software 3.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
94
1
13

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(114 citation statements)
references
References 64 publications
6
94
1
13
Order By: Relevance
“…The findings indicated that Chinese students who interact more often during online learning showed higher levels of learning satisfaction. The results are consistent with prior research conducted in faceto-face learning that interaction enhances student learning involvement and develops the sense of belonging in the learning process for students (Scagnoli, 2001), which positively affects students' learning satisfaction (Jung et al, 2002;Baber, 2021), regardless of whether it is online or face-to-face (Moore and Kearsley, 1996). Additionally, in an online environment, students leverage the technology to interact without the limitation of time, place, and space to gain knowledge and skills (Kaymak and Horzum, 2013).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The findings indicated that Chinese students who interact more often during online learning showed higher levels of learning satisfaction. The results are consistent with prior research conducted in faceto-face learning that interaction enhances student learning involvement and develops the sense of belonging in the learning process for students (Scagnoli, 2001), which positively affects students' learning satisfaction (Jung et al, 2002;Baber, 2021), regardless of whether it is online or face-to-face (Moore and Kearsley, 1996). Additionally, in an online environment, students leverage the technology to interact without the limitation of time, place, and space to gain knowledge and skills (Kaymak and Horzum, 2013).…”
Section: Discussionsupporting
confidence: 90%
“…It is a process that allows learners to seek new information and form connections with instructors, other learners, and content in their learning activities (Moore, 1989). It has been identified that learning activities are a significant element that critically determines the learners' learning outcomes (Baber, 2021). A cross-country study conducted by Baber (2020) during the COVID-19 pandemic revealed interaction as the most significant factor in examining students' online learning satisfaction and learning outcomes.…”
Section: Interactionmentioning
confidence: 99%
“…The lack of closed interaction between instructors and students as well as between students themselves can subsequently hinder whole person development (Robinson & Kakela, 2006;Swan, 2002). On the other hand, online learning that temporarily replaces conventional learning has enabled learning and whole person development to continue, despite some social distancing measures that are implemented in many countries (Baber, 2021).…”
Section: Cultivation Of Whole Person Development Through Online Learningmentioning
confidence: 99%
“…A large body of research is available on traditional learning environments (Bekele, 2010), and there is evidence that the transition from traditional to remote learning during the COVID-19 pandemic was successful (Basilaia & Kvavadze, 2020). However, minimal literature is available on the quality and effectiveness of online learning, improving student learning outcomes (Baber, 2021), and no research is available on how fear of the pandemic affects students' motivation in online learning.…”
Section: Students' Psychological Motivation and Online Learningmentioning
confidence: 99%